Analysis of Immersion-Based English Learning on Improving the Language Skills of Students at the Darussalam Gontor Modern Islamic Institution - Novitasari, Dwiana; Nurul Chojimah (Journal of English Development, 2026)
This study analyzes the implementation of immersion-based English learning at the Darussalam Gontor Modern Islamic Institution and its role in improving students' language skills, particularly speaking proficiency. The research employed a qualitative case study approach. Data analysis was conducted using the Miles and Huberman model, including data collection, data reduction, data presentation, and the drawing and verification of conclusions. The findings indicate that immersion-based learning at Darussalam Gontor Modern Islamic Institution is systematically integrated into both formal and informal educational activities through a strong bi'ah lughawiyah (language environment), high disciplinary standards, and the consistent application of the direct method. Programs such as English Week, daily vocabulary reinforcement, conversation practice, public speaking, and language-based extracurricular activities provide continuous, context-rich exposure to the English language. This immersive environment encourages active language use, reduces students' speaking anxiety, and fosters self-confidence. Although challenges such as grammatical inaccuracy and avoidance strategies were observed, these issues function as transitional stages in the development of communicative competence. Overall, immersion-based English learning at Darussalam Gontor Modern Islamic Institution effectively enhances students' language skills and positions the institution as a distinctive and successful model of English language education in Indonesia.